Effects Of Ethanolic Extract Of Cocoa On Blood Glucoseand Lipid Profile In Streptozotocin-Induced Diabetic Rats - Mohd Mokhtar, Ruzaidi Azli (2005)
This study aims to investigate the hypoglycaemic and hypocholesterolaemic properties of Malaysian cocoa (Theobroma cacao) polyphenols extract in-vivo and in-vitro. Cocoa extract (contained 190 - 286 mg total polyphenol per g of extract) was prepared from fermented and roasted (140 "C, 20 min) beans by extracting with 80% ethanol in the ratio of 1 to 10. The total phenolic content was estimated according to the Folin-Ciocalteu reagent method. The eluted individual polyphenol was monitored by using a normal-phase HPLC. Monomer is the predominant polyphenols present in cocoa extract (CE) followed by dimer and tetramer. To study the effect of CE on plasma glucose levels and lipid profiles in normal and diabetic rats, two different batches of animal (in-vivo) studies were performed. In the first batch, rats were given free excess to diet containing CE in the form of powder, while in the second batch, rats were force-fed with CE suspended in normal saline daily. The CE was given in three dosages (100, 200 and 300 mg per kg body weight) to both batches for a period of 4 weeks. The result showed that 100 mgkg and 300 mgkg CE significantly reduced (p < 0.05) the plasma glucose levels in the diabetic rats of both the first and second batch of studies. In the first batch, supplementation of 100 mgkg and 300 mglkg CE had significantly reduced (p < 0.05) the level of total cholesterol in diabetic rats. In addition, 100, 200 and 300 mgkg CE diets had significantly lowered (p < 0.05) the total triglycerides. Interestingly, this study found that plasma HDL-cholesterol had increased significantly (p < 0.05) in diabetic rats fed with 200 mgkg CE, while the LDL-cholesterol had decreased significantly (p < 0.05) in group treated with 100 mgkg CE. In the second batch, plasma cholesterol, HDL-cholesterol and LDL-cholesterol levels showed no siginificant difference in both normal and diabetic rats. Meanwhile, there was a significant decrease (p < 0.05) in plasma triglyceride level in diabetic rats. In another study, rats were pretreated with CE to investigate the protective effect of CE against streptozotocin diabetogenic action. In 200 mglkg CE pretreated rats, there was a 163% increase in plasma glucose levels, compared with a 226% increase in diabetic control rats. There were no protective effects on plasma lipid profiles in CE pretreated rats. Results also exhibited CE could normalize the body weight loss caused by STZ. BRIN-BD11 cell lines (in-vitro) were used to evaluate the effect of CE on insulin secretion. This invitro study demonstrated that CE at a concentration of 0.1 mglrnl significantly increase (p < 0.05) insulin secretion compared to control. In conclusion, the study shows that Malaysian cocoa polyphenol extract may possess potential hypoglycaernic and hypochlosterolaernic properties. Further studies are needed to elucidate the exact mechanism by which polyphenols present in CE can lower the plasma glucose levels and improved lipid profiles in diabetic rats, and stimulate insulin secretion in BRIN-BDl1 cell lines.